2003
DOI: 10.1207/s15374424jccp3201_06
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feelings Exacerbate Hostile Attributions of Intent in Highly Aggressive Boys

Abstract: Tested the hypothesis that aggressive boys' tendency to attribute hostile intentions to peers is exacerbated in a negative emotional state. Twenty-nine highly aggressive boys in special education, 12 moderately aggressive boys in regular education, and 16 nonaggressive boys in regular education inferred peers' intentions in 8 vignettes concerning ambiguous provocation by peers. Mild negative emotions were induced by unjust loss of a manipulated computer game. Half the vignettes were completed in this negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 20 publications
4
55
0
3
Order By: Relevance
“…In addition, these results converge with those of Lemerise et al (2006) who showed that rejected-aggressive children's goals and social problem-solving responses (see also Lemerise et al 2005) were more hostile when provocateurs displayed anger. Finally our findings are consistent with work from several researchers suggesting that rejected-aggressive children and adolescents have difficulty managing their anger in challenging social situations (DiLiberto et al 2002;Graham et al 1992;Hubbard et al 2002;Orobio de Castro et al 2005) and that negative arousal has a more disruptive effect on the SIP of aggressive than nonaggressive children (Dodge and Somberg 1987;Orobio de Castro et al 2003;Vitaro et al 1989). Although previous studies extended our understanding of how negative arousal affects SIP, the current study extended past research by finding effects of discrete emotions on children's goal selection.…”
Section: Mood Condition Instrumental Goals and Social Adjustmentsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, these results converge with those of Lemerise et al (2006) who showed that rejected-aggressive children's goals and social problem-solving responses (see also Lemerise et al 2005) were more hostile when provocateurs displayed anger. Finally our findings are consistent with work from several researchers suggesting that rejected-aggressive children and adolescents have difficulty managing their anger in challenging social situations (DiLiberto et al 2002;Graham et al 1992;Hubbard et al 2002;Orobio de Castro et al 2005) and that negative arousal has a more disruptive effect on the SIP of aggressive than nonaggressive children (Dodge and Somberg 1987;Orobio de Castro et al 2003;Vitaro et al 1989). Although previous studies extended our understanding of how negative arousal affects SIP, the current study extended past research by finding effects of discrete emotions on children's goal selection.…”
Section: Mood Condition Instrumental Goals and Social Adjustmentsupporting
confidence: 91%
“…However, when a "threat" was staged via an "overheard" conversation, rejected-aggressive boys made more SIP errors of presumed hostility and hostile attributions than did adjusted-nonaggressive boys (Dodge and Somberg 1987). Similar results were reported when a situational manipulation which involved unjustly losing a computer game was used (Orobio de Castro et al 2003). Finally, there is evidence that when the staged provocation was more intense (involving a "live" confederate whose behavior was quite provoking), the SIP (attributions and social problem solving) of both adjusted and rejected-aggressive first and second graders was disrupted, particularly when assessed immediately after the provocation (Vitaro et al 1989).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Among aggressive children, more hostile attributions tend to be made when a negative emotional state was induced, as opposed to a positive emotional state (Dodge & Somberg, 1987;Orobio de Castro, Slot, Bosch, Koops, & Veerman, 2003). Emotion was measured in terms of arousal reactivity by Williams, Lochman, Phillips, and Barry (2003) who found that moderately aggressive boys exhibited increased heart rate and increased hostile attributions when a threat was introduced.…”
Section: Hostile Attributions and Emotionmentioning
confidence: 99%
“…Laboratory studies likewise show that aggression, in particular, is associated with negative emotionality (e.g., anger) and limited emotional competence (e.g. low ability to identify the causes of aggression; Bohnert, Crnic, & Lim, 2003;Cole, Zahn-Waxler, Fox, Usher, & Welsh, 1996;de Castro, Slot, Bosch, Koops, & Veerman, 2003). Because difficulties in modulating emotional expressions may relate to the presence of externalizing and internalizing disorders (Keenan, 2000), the role of negative emotionality and its regulation in patient populations deserve further empirical evaluation (see Eisenberg et al, 2001).…”
mentioning
confidence: 99%